Preparation method of aluminum hydroxide powder with coarse particle size
By using raw materials such as aluminum hydroxide, sodium hydroxide and urea and polysiloxane-g-polyethylene glycol sulfonate, coarse-grain aluminum hydroxide powder is prepared, and its performance is improved through seed decomposition, which solves the problem of poor time-consuming, energy-consuming and compatibility of traditional preparation methods, and achieves high-efficiency and low-energy-consuming aluminum hydroxide preparation and modification.
Patent Information
- Application Number
- CN202411877568.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
AI Technical Summary
The existing aluminum hydroxide preparation method consumes time and energy, and has poor compatibility with polymer substrates, which affects the filling performance.
Using industrial-grade aluminum hydroxide, sodium hydroxide and urea as raw materials, coarse-grained aluminum hydroxide powder is prepared by reaction with polysiloxane-g-polyethylene glycol sulfonate, and its particle size and filling performance are improved through seed decomposition.
It significantly shortens the preparation time of aluminum hydroxide, reduces energy consumption, improves its compatibility and filling performance with polymer substrates, and is suitable for industrial production.
Smart Images

Figure CN119683662A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic powders, and in particular relates to a method for preparing coarse-grained aluminum hydroxide powder. Background Art
[0002] Thermal interface materials are a general term for materials that are filled between heating devices and heat dissipating devices to reduce contact thermal resistance and enhance heat dissipation. They are widely used in electronic communications, new energy and other fields. As electronic products develop towards lightweight and cost-effectiveness, the market demand for low-density, low-cost thermal interface materials is becoming increasingly urgent. Most thermal interface materials are filled polymer composites. The thermal conductivity of the polymer substrate is low, and it mainly relies on thermal conductive fillers to establish thermal conductive channels in the substrate. Therefore, the thermal conductivity is mainly determined by the type, morphology and filling amount of the thermal conductive filler.
[0003] Thermally conductive fillers are mainly divided into inorganic non-metallic fillers and metal fillers. The former conducts heat through lattice vibration, while the latter relies on the rapid movement of free electrons to achieve heat transfer. Since thermal interface materials usually require insulation properties, inorganic fillers have more advantages in thermal interface materials. As an inorganic non-metallic filler, aluminum hydroxide has low density (2.42g / cm3), low cost, and good insulation, which meets the current market demand for lightweight electronic products and cost control. In addition, it also has good flame retardant properties and is often used in flame retardants. It has the characteristics of smoke suppression and flame retardancy without releasing toxic gases. It is widely used in plastics, rubber, coatings, building materials and other industries.
[0004] In summary, aluminum hydroxide has a very large application value. At present, the main production methods of aluminum hydroxide are the Bayer process and the sintering process. The Bayer process is to directly dissolve bauxite under high temperature and high pressure with caustic soda; and the sintering process is to sinter various raw materials at high temperature. Although the raw materials used in these two methods are low in cost, it takes a long time and consumes a lot of energy to prepare coarse-grained aluminum hydroxide using these two methods. For example, CN101654271A discloses a method for producing sand-like alumina using sintering crude liquid, in which a sodium aluminate crude liquid is prepared by sintering, and then a primary product aluminum hydroxide is obtained by carbon fractionation, and the primary product is dissolved by the Bayer process, and a coarse-grained aluminum hydroxide is obtained after seed fractionation; first, this method requires a large amount of seed crystals, and secondly, the crystal growth rate of the seed fractionation method is 1-3 microns / day per day, so it actually takes about 30-45 days for the newly generated nuclei from the decomposition process, and multiple seed fractionation cycles are required to grow into 90 microns of aluminum hydroxide.
[0005] In the application process, although aluminum hydroxide has been widely used as a filler, its compatibility with polymer substrates is poor, and it usually needs to be modified to improve its performance. In order to overcome the time-consuming and energy-consuming problems in the traditional aluminum hydroxide preparation process, the technical solution of the present invention provides a new method for preparing coarse-grained aluminum hydroxide, which can effectively shorten the preparation time and reduce energy consumption, and simultaneously complete the modification of aluminum hydroxide during the preparation process, improve its compatibility with polymer substrates, and enhance filling performance. In addition, the raw materials used in this method are easy to obtain, the process flow is simple, and the requirements for production equipment are low, which is easy to realize industrial production. Summary of the invention
[0006] In summary, the present invention provides a method for preparing coarse-particle aluminum hydroxide powder, using industrial-grade aluminum hydroxide, sodium hydroxide and urea as raw materials to prepare coarse-particle aluminum hydroxide micropowder.
[0007] The method for preparing the coarse-grained aluminum hydroxide micropowder of the present invention comprises the following steps: (1) dissolving aluminum hydroxide in a sodium hydroxide solution to prepare sodium aluminate solution A and sodium aluminate solution C with certain concentrations; (2) adding an appropriate amount of polysiloxane-g-polyethylene glycol sulfonate to sodium aluminate solution A and stirring for a certain period of time to obtain solution B; (3) adding an appropriate amount of urea to solution B, stirring and reacting at a certain temperature, filtering, washing, and drying after the reaction is completed to obtain coarse-grained irregular aluminum hydroxide; (4) heating the solution C to the initial decomposition temperature, adding an appropriate amount of the coarse-grained irregular aluminum hydroxide obtained in step (3) as a seed crystal under stirring, and adding an appropriate amount of polysiloxane-g-polyethylene glycol sulfonate, then cooling the solution at a certain rate to the final decomposition temperature, filtering, washing, and drying to obtain coarse-grained aluminum hydroxide; the structural formula of the polysiloxane-g-polyethylene glycol sulfonate is: Among them, n=12-18, m=25-40.
[0008] The aluminum hydroxide in step (1) is common commercially available 20-70 micron irregular aluminum hydroxide.
[0009] In the step (1), the caustic ratio of the sodium aluminate solution A is 1.33-1.47, and the aluminum oxide concentration is 166-180 g / L; the caustic ratio of the sodium aluminate solution C is 1.33-1.47, and the aluminum oxide concentration is 100-120 g / L.
[0010] In the step (2), the mass ratio of polysiloxane-g-polyethylene glycol sulfonate to sodium aluminate solution A is 1‰-5‰:1, the stirring rate is 300-500r / min, and the stirring time is 20-40min.
[0011] In the step (3), the amount of urea added is 100-300 g / L, the stirring rate is 200-400 r / min, the reaction temperature is 110-125° C., and the reaction time is 2-4 h.
[0012] The washing method in step (3) is to wash with deionized water for 3-5 times, the drying temperature is 80-100° C., and the drying time is 10-16 hours.
[0013] The initial decomposition temperature of step (4) is 70° C., the stirring rate is 200-300 r / min, and the amount of coarse-grained irregular aluminum hydroxide added is 300-350 g / L.
[0014] The mass ratio of the polysiloxane-g-polyethylene glycol sulfonate to the sodium aluminate solution C in the step (4) is 0.1‰-0.3‰:1.
[0015] The cooling rate of step (4) is 0.2°C / h, and the final decomposition temperature is 58°C.
[0016] The washing method of step (4) is to wash with deionized water for 3-5 times, and then wash with anhydrous ethanol for 3-5 times, the drying temperature is 90-100° C., and the drying time is 20-24 hours.
[0017] The polysiloxane-g-polyethylene glycol sulfonate synthesis method is as follows: (1) Single-end hydrogenated silicone oil, terminal allyl epoxy polyethylene glycol and isopropanol accounting for 30% of the mass of the reactants are added into a three-necked flask, the molar ratio of single-end hydrogenated silicone oil to terminal allyl epoxy polyethylene glycol is 1:1.05, nitrogen is passed through and stirred for 15-20 minutes, then the temperature is raised to 70-80°C, and a platinum catalyst accounting for 0.002% of the monomer mass is added. The reaction time is 4-5 hours. After the reaction is completed, vacuum distillation is performed to remove isopropanol and low-boiling substances. After cooling, a light yellow liquid is obtained, which is polysiloxane-g-cycloethoxy polyethylene glycol. The reaction equation is: (2) Add polysiloxane-g-cycloethoxy polyethylene glycol and a mixed solution of isopropanol and water into a three-necked flask, the volume ratio of isopropanol to water is 2:1, and the mixed solution of isopropanol and water accounts for 60%-70% of the mass of polysiloxane-g-cycloethoxy polyethylene glycol. Stir and heat to 70-90°C, then add an appropriate amount of NaHSO3, the molar ratio of polysiloxane-g-cycloethoxy polyethylene glycol to NaHSO3 is 1:1.1-1.3, continue the reaction for 10-16 hours, and after the reaction is completed, distill under reduced pressure to remove isopropanol and water, then add anhydrous ethanol to remove the sulfonation reagent NaHSO3, filter to obtain a filtrate, and distill the filtrate under reduced pressure to remove ethanol to obtain a reddish brown liquid polysiloxane-g-polyethylene glycol sulfonate. The reaction equation is as follows:
[0018] The formation process of the coarse-grained aluminum hydroxide powder of the present invention is as follows: The urea added in step 2 of the present invention is uniformly dissolved in the sodium aluminate solution, and slowly decomposes into carbon dioxide and ammonia as the solution is heated, and reacts with sodium aluminate to generate aluminum hydroxide and sodium carbonate. Since this reaction is basically irreversible, the growth rate of aluminum hydroxide is very fast; secondly, the polysiloxane-g-polyethylene glycol sulfonate plays a bridging role to further increase the growth rate of aluminum hydroxide, and the sulfonic acid group can adsorb the decomposition product of sodium aluminate Al(OH) - 4. It accelerates the agglomeration of aluminum hydroxide complex ions and enhances the precipitation of aluminum hydroxide, so aluminum hydroxide of 90-150 microns can be prepared within 3 hours. However, since the aluminum hydroxide obtained at this time is obtained by the reaction of urea decomposition products with aluminum ions, the initial product is angular and has poor filling properties; therefore, the initial aluminum hydroxide obtained is used as a seed for seed decomposition. During the seed decomposition process, the dissolution and precipitation of aluminum hydroxide on the surface of the seed maintains a dynamic balance, gradually making the coarse-grained irregular aluminum hydroxide smooth and round, which is more conducive to filling in the polymer matrix. Secondly, polysiloxane-g-polyethylene glycol sulfonate has a powder modification effect, which can improve its compatibility and dispersibility in the polymer matrix.
[0019] The technical points and beneficial effects of the present invention are as follows: (1) Compared with common aluminum hydroxide, the coarse-grained aluminum hydroxide prepared by the present invention has better filling property and compatibility, especially in the silicone rubber system, and can improve the performance of the final product such as thermal conductivity. (2) Compared with the conventional seed decomposition method, the coarse-grained aluminum hydroxide prepared by the present invention can produce coarse-grained aluminum hydroxide with a particle size of 90-150 microns in a relatively short time (about 4 days), and has high production efficiency. The conventional seed decomposition method usually takes about 2 months, and requires multiple cycles during the process, requiring large energy consumption and high cost. (3) The production process of the present invention is simple, the equipment requirements are low, the energy consumption of the production process is low, it is easy to industrialize, and it has strong practical application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Scanning electron microscope (SEM) photo of the coarse-grained aluminum hydroxide prepared in Example 1 of the present method Figure 2 Scanning electron microscope (SEM) photo of the coarse-grained aluminum hydroxide prepared in Example 2 of this method Figure 3 Scanning electron microscope (SEM) photo of the coarse-grained aluminum hydroxide prepared in Example 3 of the present method Figure 4 Scanning electron microscope (SEM) photo of the coarse-grained aluminum hydroxide prepared in comparative example 1 of the present method Figure 5 Scanning electron microscope (SEM) photo of aluminum hydroxide prepared in comparative example 2 of this method DETAILED DESCRIPTION
[0021] The present invention is further described below in conjunction with examples. It should be noted that the following are only preferred implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications and replacements based on the technical solutions and inventive concepts provided by the present invention should be covered within the protection scope of the present invention.
[0022] The specific implementation steps of the present invention are as follows: (1) The synthesis method of polysiloxane-g-polyethylene glycol sulfonate is as follows: Single-ended hydrogenated silicone oil, terminal allyl epoxy polyethylene glycol and isopropanol accounting for 30% of the mass of the reactants are added into a three-necked flask, the molar ratio of single-ended hydrogenated silicone oil to terminal allyl epoxy polyethylene glycol is 1:1.05, nitrogen is passed through and stirred for 15-20 minutes, then the temperature is raised to 70-80°C, and a platinum catalyst accounting for 0.002% of the monomer mass is added. The reaction time is 4-5 hours. After the reaction is completed, vacuum distillation is performed to remove isopropanol and low-boiling substances. After cooling, a light yellow liquid is obtained, which is polysiloxane-g-cycloethoxy polyethylene glycol. The reaction equation is: Add polysiloxane-g-cycloethoxy polyethylene glycol and a mixed solution of isopropanol and water into a three-necked flask, the volume ratio of isopropanol and water is 2:1, and the mixed solution of isopropanol and water accounts for 60%-70% of the mass of polysiloxane-g-cycloethoxy polyethylene glycol. Stir and heat to 70-90°C, then add an appropriate amount of NaHSO3, the molar ratio of polysiloxane-g-cycloethoxy polyethylene glycol and NaHSO3 is 1:1.1-1.3, continue the reaction for 10-16h, and after the reaction is completed, distill under reduced pressure to remove isopropanol and water, then add anhydrous ethanol to remove the sulfonation reagent NaHSO3, filter to obtain a filtrate, and distill the filtrate under reduced pressure to remove ethanol to obtain a reddish brown liquid polysiloxane-g-polyethylene glycol sulfonate. The reaction equation is as follows: (2) Preparation of coarse-grained aluminum hydroxide: Aluminum hydroxide is dissolved in sodium hydroxide solution to prepare sodium aluminate solution A with a caustic ratio of 1.33-1.47 and an aluminum oxide concentration of 166-180 g / L; and sodium aluminate solution with a caustic ratio of 1.33-1.47 and an aluminum oxide concentration of 100-120 g / L; an appropriate amount of polysiloxane-g-polyethylene glycol sulfonate is added to the sodium aluminate solution A, the polysiloxane-g-polyethylene glycol sulfonate accounting for 1‰-5‰ of the mass of the sodium aluminate solution A, and the mixture is stirred at a rate of 300-500 r / min for 20-40 min to obtain solution B; 100-300 g / L of urea is added to solution B, and the mixture is stirred at a rate of 200-400 r / min and heated to 400 °C. 110-125°C, react for 2-4 hours, filter, wash with deionized water 3-5 times, dry at 80-100°C for 10-16h to obtain coarse-grained irregular aluminum hydroxide; then heat solution C to 70°C, add 300-350g / L of coarse-grained irregular aluminum hydroxide as a seed under stirring at 200-300r / min, and add an appropriate amount of polysiloxane-g-polyethylene glycol sulfonate, the polysiloxane-g-polyethylene glycol sulfonate accounts for 0.1‰-0.3‰ of the mass of sodium aluminate solution C, then cool to 58°C at a rate of 0.2°C / h, filter, wash with deionized water 3-5 times, then wash with anhydrous ethanol 3-5 times, and place in a 90-100°C oven to dry for 20-24 hours.
[0023] Example 1 (1) The synthesis method of polysiloxane-g-polyethylene glycol sulfonate is as follows: single-end hydrogen-containing silicone oil, terminal allyl epoxy polyethylene glycol and isopropanol accounting for 30% of the mass of the reactants are added into a three-necked flask, the molar ratio of the single-end hydrogen-containing silicone oil to the terminal allyl epoxy polyethylene glycol is 1:1.05, nitrogen is passed through and stirred for 15 minutes, then the temperature is raised to 70°C, and a platinum catalyst accounting for 0.002% of the monomer mass is added. The reaction time is 4 hours. After the reaction is completed, vacuum distillation is performed to remove isopropanol and low-boiling substances, and a light yellow liquid is obtained after cooling, namely polysiloxane-g-cycloethoxy polyethylene glycol; polysiloxane-g-cycloethoxy polyethylene glycol and A mixed solution of isopropanol and water is added into a three-necked flask, the volume ratio of isopropanol and water is 2:1, and the mixed solution of isopropanol and water accounts for 70% of the mass of polysiloxane-g-cycloethoxypolyethylene glycol. The mixture is stirred and heated to 90°C, and then an appropriate amount of NaHSO3 is added, and the molar ratio of polysiloxane-g-cycloethoxypolyethylene glycol and NaHSO3 is 1:1.1. The reaction is continued for 10 hours. After the reaction is completed, it is distilled under reduced pressure to remove isopropanol and water, and then anhydrous ethanol is added to remove the sulfonation reagent NaHSO3. Filter to obtain a filtrate, and the filtrate is distilled under reduced pressure to remove ethanol to obtain a reddish-brown liquid polysiloxane-g-polyethylene glycol sulfonate. (2) Preparation of coarse-grained aluminum hydroxide: Aluminum hydroxide was dissolved in sodium hydroxide solution to prepare sodium aluminate solution A with a caustic ratio of 1.33 and an aluminum oxide concentration of 166 g / L; and sodium aluminate solution C with a caustic ratio of 1.33 and an aluminum oxide concentration of 120 g / L; an appropriate amount of polysiloxane-g-polyethylene glycol sulfonate was added to the sodium aluminate solution A, the polysiloxane-g-polyethylene glycol sulfonate accounting for 1‰ of the mass of the sodium aluminate solution A, and the mixture was stirred at a rate of 300 r / min for 20 min to obtain solution B; 100 g / L of urea was added to solution B, and the mixture was stirred at a rate of 200 r / min for 1 min. The mixture was heated to 110°C, reacted for 2 hours, filtered, washed with deionized water for 5 times, and dried at 80°C for 16 hours to obtain coarse-grained irregular aluminum hydroxide; then the solution C was heated to 70°C, and 300 g / L of coarse-grained irregular aluminum hydroxide was added as a seed under stirring at 200 r / min, and an appropriate amount of polysiloxane-g-polyethylene glycol sulfonate was added, and the polysiloxane-g-polyethylene glycol sulfonate accounted for 0.1‰ of the mass of the sodium aluminate solution C, and then cooled to 58°C at a rate of 0.2°C / h, filtered, washed with deionized water for 5 times, and then washed with anhydrous ethanol for 5 times, and dried in a 90°C oven for 24 hours.
[0024] Example 2 (1) The synthesis method of polysiloxane-g-polyethylene glycol sulfonate is as follows: single-end hydrogen-containing silicone oil, terminal allyl epoxy polyethylene glycol and isopropanol accounting for 30% of the mass of the reactants are added into a three-necked flask, the molar ratio of the single-end hydrogen-containing silicone oil to the terminal allyl epoxy polyethylene glycol is 1:1.05, nitrogen is passed through and stirred for 20 minutes, then the temperature is raised to 80°C, and a platinum catalyst accounting for 0.002% of the monomer mass is added. The reaction time is 5 hours. After the reaction is completed, vacuum distillation is performed to remove isopropanol and low-boiling substances, and a light yellow liquid is obtained after cooling, namely polysiloxane-g-cycloethoxy polyethylene glycol; polysiloxane-g-cycloethoxy polyethylene glycol and A mixed solution of isopropanol and water is added into a three-necked flask, the volume ratio of isopropanol and water is 2:1, and the mixed solution of isopropanol and water accounts for 60% of the mass of polysiloxane-g-cycloethoxypolyethylene glycol. The mixture is stirred and heated to 70°C, and then an appropriate amount of NaHSO3 is added, and the molar ratio of polysiloxane-g-cycloethoxypolyethylene glycol to NaHSO3 is 1:1.3. The reaction is continued for 16 hours. After the reaction is completed, it is distilled under reduced pressure to remove isopropanol and water, and then anhydrous ethanol is added to remove the sulfonation reagent NaHSO3. Filter to obtain a filtrate, and the filtrate is distilled under reduced pressure to remove ethanol to obtain a reddish-brown liquid polysiloxane-g-polyethylene glycol sulfonate. (2) Preparation of coarse-grained aluminum hydroxide: Aluminum hydroxide was dissolved in sodium hydroxide solution to prepare sodium aluminate solution A with a caustic ratio of 1.42 and an aluminum oxide concentration of 174 g / L; and sodium aluminate solution C with a caustic ratio of 1.42 and an aluminum oxide concentration of 110 g / L; an appropriate amount of polysiloxane-g-polyethylene glycol sulfonate was added to the sodium aluminate solution A, the polysiloxane-g-polyethylene glycol sulfonate accounting for 3‰ of the mass of the sodium aluminate solution A, and the mixture was stirred at a rate of 400 r / min for 30 min to obtain solution B; 200 g / L of urea was added to solution B, and the mixture was stirred at a rate of 300 r / min for 1 h. The mixture was heated to 120°C, reacted for 3 hours, filtered, washed with deionized water for 4 times, and dried at 90°C for 13 hours to obtain coarse-grained irregular aluminum hydroxide; then the solution C was heated to 70°C, and 325 g / L of coarse-grained irregular aluminum hydroxide was added as a seed under stirring at 250 r / min, and an appropriate amount of polysiloxane-g-polyethylene glycol sulfonate was added, and the polysiloxane-g-polyethylene glycol sulfonate accounted for 0.2‰ of the mass of the sodium aluminate solution C, and then cooled to 58°C at a rate of 0.2°C / h, filtered, washed with deionized water for 4 times, and then washed with anhydrous ethanol for 4 times, and dried in a 95°C oven for 22 hours.
[0025] Example 3 (1) The synthesis method of polysiloxane-g-polyethylene glycol sulfonate is as follows: single-end hydrogen-containing silicone oil, terminal allyl epoxy polyethylene glycol and isopropanol accounting for 30% of the mass of the reactants are added into a three-necked flask, the molar ratio of the single-end hydrogen-containing silicone oil to the terminal allyl epoxy polyethylene glycol is 1:1.05, nitrogen is passed through and stirred for 20 minutes, then the temperature is raised to 80°C, and a platinum catalyst accounting for 0.002% of the monomer mass is added. The reaction time is 5 hours. After the reaction is completed, vacuum distillation is performed to remove isopropanol and low-boiling substances, and a light yellow liquid is obtained after cooling, namely polysiloxane-g-cycloethoxy polyethylene glycol; polysiloxane-g-cycloethoxy polyethylene glycol and A mixed solution of isopropanol and water is added into a three-necked flask, the volume ratio of isopropanol and water is 2:1, and the mixed solution of isopropanol and water accounts for 70% of the mass of polysiloxane-g-cycloethoxypolyethylene glycol. The mixture is stirred and heated to 70°C, and then an appropriate amount of NaHSO3 is added, and the molar ratio of polysiloxane-g-cycloethoxypolyethylene glycol to NaHSO3 is 1:1.2. The reaction is continued for 12 hours. After the reaction is completed, the isopropanol and water are removed by vacuum distillation, and then anhydrous ethanol is added to remove the sulfonation reagent NaHSO3. The mixture is filtered to obtain a filtrate, and the filtrate is subjected to vacuum distillation to remove ethanol to obtain a reddish-brown liquid polysiloxane-g-polyethylene glycol sulfonate. (2) Preparation of coarse-grained aluminum hydroxide: Aluminum hydroxide was dissolved in sodium hydroxide solution to prepare sodium aluminate solution A with a caustic ratio of 1.47 and an aluminum oxide concentration of 180 g / L; and sodium aluminate solution C with a caustic ratio of 1.47 and an aluminum oxide concentration of 120 g / L; an appropriate amount of polysiloxane-g-polyethylene glycol sulfonate was added to the sodium aluminate solution A, the polysiloxane-g-polyethylene glycol sulfonate accounting for 5‰ of the mass of the sodium aluminate solution A, and the solution was stirred at a rate of 500 r / min for 40 min to obtain solution B; 300 g / L of urea was added to solution B, and the solution was stirred at a rate of 400 r / min and heated. To 125°C, react for 4 hours, filter, wash 3 times with deionized water, and dry at 100°C for 10 hours to obtain coarse-grained irregular aluminum hydroxide; then heat solution C to 70°C, add 350g / L of coarse-grained irregular aluminum hydroxide as a seed under stirring at 300r / min, and add an appropriate amount of polysiloxane-g-polyethylene glycol sulfonate, the polysiloxane-g-polyethylene glycol sulfonate accounts for 0.3‰ of the mass of sodium aluminate solution C, then cool to 58°C at a rate of 0.2°C / h, filter, wash 3 times with deionized water, then wash 3 times with anhydrous ethanol, and place in a 100°C oven to dry for 20 hours.
[0026] Comparative Example 1 (Example 3 did not carry out sodium aluminate seeding) The difference between Comparative Example 1 and Example 3 is that the irregular aluminum hydroxide prepared by urea and sodium aluminate solution A is not put into the sodium aluminate solution C as a seed for seed decomposition. The specific preparation method is as follows: (1) The synthesis method of polysiloxane-g-polyethylene glycol sulfonate is as follows: single-end hydrogen-containing silicone oil, terminal allyl epoxy polyethylene glycol and isopropanol accounting for 30% of the mass of the reactants are added into a three-necked flask, the molar ratio of the single-end hydrogen-containing silicone oil to the terminal allyl epoxy polyethylene glycol is 1:1.05, nitrogen is passed through and stirred for 20 minutes, then the temperature is raised to 80°C, and a platinum catalyst accounting for 0.002% of the monomer mass is added. The reaction time is 5 hours. After the reaction is completed, vacuum distillation is performed to remove isopropanol and low-boiling substances, and a light yellow liquid is obtained after cooling, namely polysiloxane-g-cycloethoxy polyethylene glycol; polysiloxane-g-cycloethoxy polyethylene glycol and A mixed solution of isopropanol and water is added into a three-necked flask, the volume ratio of isopropanol and water is 2:1, and the mixed solution of isopropanol and water accounts for 70% of the mass of polysiloxane-g-cycloethoxypolyethylene glycol. The mixture is stirred and heated to 70°C, and then an appropriate amount of NaHSO3 is added, and the molar ratio of polysiloxane-g-cycloethoxypolyethylene glycol to NaHSO3 is 1:1.2. The reaction is continued for 12 hours. After the reaction is completed, the isopropanol and water are removed by vacuum distillation, and then anhydrous ethanol is added to remove the sulfonation reagent NaHSO3. The mixture is filtered to obtain a filtrate, and the filtrate is subjected to vacuum distillation to remove ethanol to obtain a reddish-brown liquid polysiloxane-g-polyethylene glycol sulfonate. (2) Preparation of coarse-grained aluminum hydroxide: Aluminum hydroxide is dissolved in sodium hydroxide solution to obtain a sodium aluminate solution A with a caustic ratio of 1.47 and an alumina concentration of 180 g / L; an appropriate amount of polysiloxane-g-polyethylene glycol sulfonate is added to the sodium aluminate solution A, where the polysiloxane-g-polyethylene glycol sulfonate accounts for 5‰ of the mass of the sodium aluminate solution A, and the solution is stirred at a rate of 500 r / min for 40 min to obtain a solution B; 300 g / L of urea is added to the solution B, and the solution is stirred at a rate of 400 r / min and heated to 125°C, reacted for 4 hours, filtered, washed with deionized water three times, and dried at 100°C for 10 hours to obtain coarse-grained irregular aluminum hydroxide.
[0027] Comparative Example 2 (polysiloxane-g-polyethylene glycol sulfonate is not used as an auxiliary agent) The difference between Comparative Example 1 and Example 3 is that polysiloxane-g-polyethylene glycol sulfonate is not added. The specific preparation method is as follows: Preparation of coarse-grained aluminum hydroxide: aluminum hydroxide is dissolved in sodium hydroxide solution to obtain a sodium aluminate solution A with a caustic ratio of 1.47 and an alumina concentration of 180 g / L; and a sodium aluminate solution C with a caustic ratio of 1.47 and an alumina concentration of 120 g / L is obtained; 300 g / L of urea is added to solution A, and the solution is heated to 125°C with stirring at a rate of 400 r / min, reacted for 4 hours, filtered, washed with deionized water 3 times, and dried at 100°C for 10 hours to obtain coarse-grained irregular aluminum hydroxide; then solution C is heated to 70°C, and 350 g / L of coarse-grained irregular aluminum hydroxide is added as a seed crystal under stirring at 300 r / min, and then cooled to 58°C at a rate of 0.2°C / h, filtered, washed with deionized water 3 times, and then washed with anhydrous ethanol 3 times, and placed in a 100°C oven to dry for 20 hours.
[0028] Blank example The blank example is commercially available 150 μm irregular aluminum hydroxide.
[0029] The products obtained in Examples 1-3, Comparative Examples 1-2 and Blank Examples were subjected to performance testing and characterization (Table 1 and accompanying drawings), and the performance testing and characterization methods are as follows: The test method for the maximum filling amount is as follows: first, evenly mix the aluminum hydroxide to be tested and 5-micron spherical aluminum in a mass ratio of 4:6, and continuously add the mixed powder into 100 parts of 350cp vinyl silicone oil. After preliminary dispersion, place it in a vacuum stirring degassing machine, set the speed to 600r / min, and the stirring time to 2min, until the colloid becomes a hard mass and it is difficult to continue filling. The maximum filling amount can be obtained. Powder oil absorption test method: weigh 2g powder sample and 4g dioctyl phthalate (DOP) in a centrifuge tube, ultrasonically vibrate for 15 minutes to fully wet the powder, then put the centrifuge tube into the centrifuge, set the speed to 3000r / min, and the centrifugation time to 1h. After the centrifugation, take out the centrifuge tube and invert it to let the excess DOP flow out, wipe off the residual DOP in the centrifuge tube, weigh the mass of the centrifuge tube, and calculate the powder oil absorption value (g / 100g). Morphology testing method: The microscopic morphology of the samples was observed using a COXEM desktop scanning electron microscope. Particle size test method: LS-609 laser particle size analyzer was used to test the sample particle size, focusing on the change of D50.
[0030] Table 1
[0031] According to the performance characterization and electron microscope scanning results (1) In terms of particle size: As shown in Example 3 and Comparative Examples 1 and 2, since the comparative example has not undergone seed decomposition modification, the irregularity is large and the oil absorption value is high. In addition, since Example 3 has undergone seed decomposition modification, the crystals grow during the seed decomposition process, so the particle size increases slightly. However, since no additives are added to Comparative Example 2, there is no good agglomeration and growth in the first step of the reaction of sodium aluminate and urea, and no additives are added in the second part of the seed to help complexation and precipitation, so the particle size of Comparative Example 2 is significantly smaller than that of Example 3 and Comparative Example 2. (2) In terms of oil absorption: In Examples 1, 2, and 3, the particle size gradually increases due to the adjustment of process parameters, and the oil absorption gradually decreases as the particle size increases. In Comparative Example 1, since no seed shaping is performed, the overall roundness is reduced and the irregularity increases relative to Example 3, and the oil absorption is greater than that of Example 3. The particle size of Comparative Example 2 is obviously smaller and the surface is not smooth and round, so the oil absorption is significantly increased. (3) In terms of filling amount: Since the particle size of Examples 1, 2, and 3 is too large, they are mixed with 5-micron aluminum spheres in a certain proportion. When the maximum filling amount of the mixed powder is tested, the particle size of Examples 1, 2, and 3 gradually increases due to the adjustment of process parameters. Therefore, the maximum filling number increases with the increase of particle size. Compared with Example 3, the overall roundness of Comparative Example 1 decreases, the irregularity increases, and the maximum filling amount decreases significantly. The surface particle size of Comparative Example 2 is smaller, but more irregular, the surface is rougher, and no additives are used for modification, so the maximum filling amount decreases significantly. Compared with the blank example, Example 3 is modified with additives, so the maximum filling amount of Example 3 is significantly higher than that of the blank example.
Claims
1. A method for preparing coarse-grained aluminum hydroxide powder, characterized in that: The following steps are involved: (1) dissolving aluminum hydroxide in a sodium hydroxide solution to prepare sodium aluminate solution A and sodium aluminate solution C with certain concentrations; (2) adding an appropriate amount of polysiloxane-g-polyethylene glycol sulfonate to sodium aluminate solution A and stirring for a certain period of time to obtain solution B; (3) adding an appropriate amount of urea to solution B, stirring and reacting at a certain temperature, filtering, washing, and drying after the reaction is completed to obtain coarse-grained irregular aluminum hydroxide; (4) heating solution C to the initial decomposition temperature, adding an appropriate amount of the coarse-grained irregular aluminum hydroxide obtained in step (3) as a seed crystal, and adding an appropriate amount of polysiloxane-g-polyethylene glycol sulfonate under stirring conditions, and then cooling the solution at a certain rate to the final decomposition temperature, filtering, washing, and drying to obtain coarse-grained aluminum hydroxide; The structural formula of the polysiloxane-g-polyethylene glycol sulfonate is: Among them, n=12-18, m=25-40.
2. The method for preparing a coarse-grained aluminum hydroxide powder according to claim 1, characterized in that: The aluminum hydroxide in step (1) is common commercially available 20-70 micron irregular aluminum hydroxide.
3. The method for preparing a coarse-grained aluminum hydroxide powder according to claim 1, characterized in that: In the step (1), the caustic ratio of the sodium aluminate solution A is 1.33-1.47, and the aluminum oxide concentration is 166-180 g / L; the caustic ratio of the sodium aluminate solution C is 1.33-1.47, and the aluminum oxide concentration is 100-120 g / L.
4. The method for preparing a coarse-grained aluminum hydroxide powder according to claim 1, characterized in that: In the step (2), the mass ratio of polysiloxane-g-polyethylene glycol sulfonate to sodium aluminate solution A is 1‰-5‰:1, the stirring rate is 300-500r / min, and the stirring time is 20-40min.
5. The method for preparing a coarse-grained aluminum hydroxide powder according to claim 1, characterized in that: In the step (3), the amount of urea added is 100-300 g / L, the stirring rate is 200-400 r / min, the reaction temperature is 110-125° C., and the reaction time is 2-4 h.
6. The method for preparing a coarse-grained aluminum hydroxide powder according to claim 1, characterized in that: The washing method in step (3) is to wash with deionized water for 3-5 times, the drying temperature is 80-100° C., and the drying time is 10-16 hours.
7. The method for preparing a coarse-grained aluminum hydroxide powder according to claim 1, characterized in that: The initial decomposition temperature of step (4) is 70° C., the stirring rate is 200-300 r / min, and the amount of coarse-grained irregular aluminum hydroxide added is 300-350 g / L.
8. The method for preparing a coarse-grained aluminum hydroxide powder according to claim 1, characterized in that: The mass ratio of the polysiloxane-g-polyethylene glycol sulfonate to the sodium aluminate solution C in the step (4) is 0.1‰-0.3‰:
1.
9. The method for preparing a coarse-grained aluminum hydroxide powder according to claim 1, characterized in that: The cooling rate of step (4) is 0.2°C / h, and the final decomposition temperature is 58°C.
10. The method for preparing a coarse-grained aluminum hydroxide powder according to claim 1, characterized in that: The washing method of step (4) is to wash with deionized water for 3-5 times, and then wash with anhydrous ethanol for 3-5 times, the drying temperature is 90-100° C., and the drying time is 20-24 hours.
11. The method for preparing a coarse-grained aluminum hydroxide powder according to claim 1, characterized in that: The polysiloxane-g-polyethylene glycol sulfonate synthesis method is as follows: (1) Single-end hydrogenated silicone oil, terminal allyl epoxy polyethylene glycol and isopropanol accounting for 30% of the mass of the reactants are added into a three-necked flask, the molar ratio of single-end hydrogenated silicone oil to terminal allyl epoxy polyethylene glycol is 1:1.05, nitrogen is passed through and stirred for 15-20 minutes, then the temperature is raised to 70-80°C, and a platinum catalyst accounting for 0.002% of the monomer mass is added. The reaction time is 4-5 hours. After the reaction is completed, vacuum distillation is performed to remove isopropanol and low-boiling substances. After cooling, a light yellow liquid is obtained, which is polysiloxane-g-cycloethoxy polyethylene glycol. The reaction equation is: (2) Add polysiloxane-g-cycloethoxy polyethylene glycol and a mixed solution of isopropanol and water into a three-necked flask, the volume ratio of isopropanol to water is 2:1, and the mixed solution of isopropanol and water accounts for 60%-70% of the mass of polysiloxane-g-cycloethoxy polyethylene glycol. Stir and heat to 70-90°C, then add an appropriate amount of NaHSO3, the molar ratio of polysiloxane-g-cycloethoxy polyethylene glycol to NaHSO3 is 1:1.1-1.3, continue the reaction for 10-16 hours, and after the reaction is completed, distill under reduced pressure to remove isopropanol and water, then add anhydrous ethanol to remove the sulfonation reagent NaHSO3, filter to obtain a filtrate, and distill the filtrate under reduced pressure to remove ethanol to obtain a reddish brown liquid polysiloxane-g-polyethylene glycol sulfonate. The reaction equation is as follows:
Citation Information
Patent Citations
Method for producing sandy alumina from crude liquid by sintering method
CN101654271A